2022
DOI: 10.1111/exd.14575
|View full text |Cite
|
Sign up to set email alerts
|

Golgin A7 family member B ( GOLGA7B ) is a plausible novel gene associating high glycaemic index diet with acne vulgaris

Abstract: While the IGF1/FoxO1/mTORC1 signalling pathway is a well‐established nutrigenomic link between high glycaemic index (GI)/glycaemic load (GL) diet and acne vulgaris, other signalling pathways remain elusive. Therefore, we aimed to investigate other genes that are involved in the high GI/GL diet‐acne link, using our Singapore/Malaysia population epidemiological, genomics and transcriptomics data. High GI/GL dietary habit of 3207 acne cases (1869 and 1341 further classified into severity and scarring grades, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…In darker skin phototypes, there appears to be a greater subclinical inflammatory response, even in noninflammatory lesions, which is thought to trigger an exaggerated post inflammatory hyperpigmentation (PIH) response and keloid scarring (31), this study found that adolescents of indigenous ethnicity had fewer repercussions from acne. Among the adolescents studied aged 12-17 years, moreover, those who had a parent or siblings with acne also had more acne-related repercussions, knowing that positive family history is a strong predisposing factor in influencing acne presentation, severity and scarring (32). Parental acne was significantly associated with acne presentation and moderate/severe acne, while sibling acne was significantly associated with grade 3/4 scarring (33).…”
Section: Discussionmentioning
confidence: 93%
“…In darker skin phototypes, there appears to be a greater subclinical inflammatory response, even in noninflammatory lesions, which is thought to trigger an exaggerated post inflammatory hyperpigmentation (PIH) response and keloid scarring (31), this study found that adolescents of indigenous ethnicity had fewer repercussions from acne. Among the adolescents studied aged 12-17 years, moreover, those who had a parent or siblings with acne also had more acne-related repercussions, knowing that positive family history is a strong predisposing factor in influencing acne presentation, severity and scarring (32). Parental acne was significantly associated with acne presentation and moderate/severe acne, while sibling acne was significantly associated with grade 3/4 scarring (33).…”
Section: Discussionmentioning
confidence: 93%
“…Woodley et al. showed that S-acylated GOLGA7B could interact with and stabilize DHHC5 at the plasma membrane to enhance cell adhesion and restrain cell scatter ( 40 ). Loss of cell adhesion causes loss of contact inhibition, which results in increased cell migration, cell proliferation and cancer progression ( 41 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we derived a novel dietary score (QDGIS) to study the association between GI intake and AD. QDGIS is based on the summation of the GI value and intake frequency of the low and high GI foods that were classified with reference to the international tables of GI and glycaemic load values by Atkinson et al [25, 26]. A specific score was assigned for the frequency of GI foods consumption in terms of the number of times/week based on the rubrics by Manousos et al [27].…”
Section: Methodsmentioning
confidence: 99%